Effect of applying nursing-based cognitive defusion techniques on mindful awareness, cognitive fusion, and believability of delusions among clients with schizophrenia: a randomized control trial - El-Ashry, Ayman Mohamed; Abd Elhay, Eman Sameh; Taha, Samah Mohamed; Khedr, Mahmoud Abdelwahab; Attalla Mansour, Feby Saad; Alabdullah, Amany Anwar Saeed; Farghaly Abdelaliem, Sally Mohammed; El-Sayed, Mona Metwally (Frontiers in Psychiatry, 2024)
Background Applying cognitive defusion techniques to enduring psychotic symptoms, such as delusions, presents both a challenge and a promising opportunity for psychiatric nurses to manage delusions among schizophrenia clients. Objective This study aimed to examine the impact of cognitive defusion techniques on psychological flexibility, mindful awareness, cognitive fusion, and the believability of delusions in schizophrenia clients. Methodology This study used a single-blind, parallel-arm Randomized Controlled Trial design. Over five weeks, 70 clients with schizophrenia were randomized to either the cognitive defusion intervention group (n = 35) or the control group (n = 35). Findings The participants showed significant reductions in the believability of delusions, cognitive fusion, and psychological inflexibility immediately after the intervention and at follow-up. Notable enhancements were observed in cognitive defusion and mindfulness awareness abilities. Conclusion Cognitive defusion techniques positively affect schizophrenia clients who struggle with persistent delusional beliefs. This underscores the importance of further investigating this approach to decrease the intensity of delusions as part of a comprehensive therapeutic intervention. Psychiatric nurses must receive training in “cognitive defusion skills” to aid schizophrenia clients in becoming more aware of their emotions and modifying their coping strategies for delusional beliefs. On August 3, 2023, the research was retrospectively registered under the reference number NCT05759091 as a randomized clinical trial. Clinical trial registration https://classic.clinicaltrials.gov/ct2/show/NCT05759091, identifier NCT05759091.